SYSTEMATIC LITERATURE REVIEW DENGAN ANALISIS BIBLIOMETRIK PADA TOPIK POULTRY FEED - Supriadi, Supriadi; Yuadi, Imam (Universitas Muhammadiyah Metro, 2023)
Abstrak: Populasi manusia semakin banyak, hal ini berbanding lurus dengan banyaknya makanan yang harus disediakan. Salah satu sumber makanan protein hewani yang dikonsumsi manusia adalah dari binatang unggas seperti ayam, itik, sapi. Penelitian makanan unggas dan makanan ternak menjadi perhatian bagi peneliti dan pemangku kepentingan agar makanan yang dikonsumsi hewan tidak membahayakan bagi ternak juga tidak membawa efek samping bagi manusia yang mengonsumsinya. Tujuan penelitian bibliometric ini adalah untuk mengetahui perkembangan penelitian tentang poultry feed. Penelitian ini mengambil data dari scopus (scopus.com) dengan keywords poultry feed mulai tahun 2013 sampai 2022. Dari pencarian ini didapat jurnal ilmiah sebanyak 1.931. Penulis mengeluarkan review, conference paper, book chapter dan letter. Terakhir penulis memilih subject area agricultural & biological sciences. Dari sini penulis mendapat data sebanyak 495 untuk dianalisis. Penelitian ini menggunakan analisis bibliometrik dan VOSViewer. Hasil analisa diketahui negara United States menjadi negara terbanyak mempublish jurnal poultry feed. University of Veterinary and Animal Sciences, Lahore Pakistan menjadi universitas terbanyak mempublish jurnal ini dan Kenis, M dan Mahata, M.E adalah author yang paling banyak mempublish jurnal ini. Dalam 10 tahun terakhir jurnal mengalami kenaikan hampir 3 kali lipat. Kata yang paling dibicarakan dalam penelitian ada 3 cluster yaitu treatment, sample, experiment. Kata kunci: Agricultural and Biological Sciences, Bibliometrics, Poultry Feed, VOSviewer Abstrack: The human population is increasing, this is directly proportional to the amount of food that must be provided. One source of animal protein food consumed by humans is from poultry such as chickens, ducks, cows. Research on poultry and livestock feed is a concern for researchers and stakeholders so that the food consumed by animals is not harmful to livestock nor does it have side effects for humans who consume it. The purpose of this bibliometric research is to find out the development of research on poultry feed. This study retrieved data from Scopus (scopus.com) with the keywords poultry feed from 2013 to 2022. This search yielded 1,931 scientific journals. The author issues reviews, conference papers, book chapters and letters. Finally, the author chose the subject area of agricultural & biological sciences. From here the writer got 495 data to be analyzed. This study uses bibliometric analysis and VOSViewer. The results of the analysis show that the United States is the country with the most publications in poultry feed journals. University of Veterinary and Animal Sciences, Lahore Pakistan is the most published university in this journal and Kenis, M and Mahata, M.E are the authors that have published the most in this journal. In the last 10 years journals have increased almost 3 times. The most discussed words in research are 3 clusters, namely treatment, sample, experiment. Key word: Agricultural and Biological Sciences, Bibliometrics, Poultry Feed, VOSviewer.